Pengaruh Budaya Organisasi dan Kepuasan Kerja terhadap Kinerja Pegawai dengan Motivasi Kerja sebagai Variabel Mediasi - Anisa Nur Sa’Ban; Yusuf Montundu; Nursaban Rommy Suleman (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
Employee performance is a key factor in achieving organizational goals. A strong organizational culture and high job satisfaction are believed to be able to encourage employee work motivation, which ultimately impacts performance improvement. Therefore, it is important to examine the influence of culture. This study aims to examine the extent to which organizational culture and job satisfaction influence employee performance, with work motivation as a variable that acts as a mediator. The research approach uses a quantitative method with Partial Least Square (PLS) analysis through the Smart PLS application. The entire population, namely 52 employees of the Konawe Regency District Attorney's Office, were involved as respondents. This study includes four variables: organizational culture, job satisfaction, work motivation, and employee performance. Data collection was conducted using a questionnaire with a Likert scale. The results of the mediation analysis indicate that work motivation does not act as a mediator in the relationship between organizational culture and employee performance. This is evident from the p-value of 0.137 and the path coefficient of 0.074, which is not significant at the 95% confidence level. The p-value of 0.027 indicates the significance of the relationship. Thus, job satisfaction not only directly influences performance but also indirectly through the resulting increased work motivation.